Jurnal Penyuluhan: Pengelolaan Kelembagaan Lelang Lebak Lebung dan Perilaku Nelayan di Kabupaten Muara Enim Provinsi Sumatera Selatan - Enik Afri Yanti, Arif Satria, Basita Ginting Sugihen (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The study aims to (1) Analyzing attitude of the fishermen towards management system in Lebak Lebung (knowladge, behaviour, and manner), (2) to describing auction system of Lebak Lebung, (3) and to analyze the external and internal characteristic between the institutional and the fishermen towards open waters managed in Lebak Lebung.